Etude Sedimentologique Et Stratigraphique Du Remplissage Du Grand Porche Du Gisement De Montgaudier, Charente, France - Boukhir Mohammed; Chaouni Abdel-Ali; Lahrach Abderrahim (European Scientific Journal, ESJ, 2017)
The sedimentological study of the deposits accumulated at the level of the two sectors of the Grand Porche of Montgaudier allowed establishing a stratigraphic synthesis of the deposits in this part of the filling of this deposit and the paleoclimatic conditions of the establishment of the different types of sediments. The systematic analyzes carried out on samples taken from the two sectors I and II revealed their origins: allochthonous and autochthonous. The data from these sedimentological analyzes of this filling also revealed the conditions and the factors which led to the establishment of these deposits. Finally, these stratigraphic studies allowed establishing a chronological framework relative to the chronology of the deposits of the adjacent loci, 8 and 6, attributed to the old würm and the Riss-würm.